Lentibulariaceae from the Viruá National Park in the northern Amazon, Roraima, Brazil - Costa, Suzana Maria; Bittrich, Volker; Do Amaral, Maria Do Carmo Estanislau (Phytotaxa, 2016)
Lentibulariaceae is the family with the second highest number of species in the Viruá National Park (VNP) according to a recent floristic survey of the aquatic and palustrine angiosperms there. The aim of the present study is to provide identification material and information on those species of Lentibulariaceae. Species descriptions were based on recent vouchers collected by the authors and previous collections deposited in various herbaria. We present keys, brief descriptions and images, comments on morphology and the geographic distribution of three species of Genlisea and 22 species of Utricularia. The eight new occurrences raise the number of known species for the family in Roraima to 39. The species composition of the Lentibulariaceae in VNP shows a close similarity with that one of the family on the Guiana Shield.